Remarkable enhancement of ambient-air electrical conductivity of the perylenediimide π-stacks isolated in the flexible films of a hydrogen-bonded polymer1. Issue 79 (28th August 2015) - Supur, Mustafa; Yurtsever, Ayhan; Akbey, Ümit
<x xml:space="preserve">Abstract</x> N, N′-di(2-(trimethylammoniumiodide)ethylene) perylenediimide (TAIPDI), forming extensive π-stacks through the strong π–π interactions of large π-planes, was isolated in the hydrogen-bonding milieu of polyvinyl alcohol (PVA) from aqueous solutions.